2005
DOI: 10.2134/jeq2004.0301
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamically Based Method to Quantify True Sorption Hysteresis

Abstract: Sorption of organic chemicals to soils and sediments often shows true hysteresis (i.e., nonsingularity of the sorption-desorption isotherm not attributable to known experimental artifacts). Since true sorption hysteresis is fundamentally important to contaminant fate, a way to quantify it is desirable. Previously proposed indices of hysteresis are empirical and usually depend on the isotherm model. True sorption hysteresis to synthetic and natural organic solids has been attributed to irreversible alteration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 58 publications
5
145
1
2
Order By: Relevance
“…Most prevalent theories therein include physical entrapment within micro-and nanopores, as well as irreversible pore deformation. It was declared that formation of meta-stable states of adsorbate in fixed mesopores on external surfaces or in the internal voids of soil organic matter was largely responsible for the great entrapment of PAHs in humin [7]. However, it was also suggested that pore deformation plays a major role to the observed hysteresis in kerogen compared to physical entrapment of sorbate molecules [36].…”
Section: Possible Mechanisms Contributing To Desorption Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Most prevalent theories therein include physical entrapment within micro-and nanopores, as well as irreversible pore deformation. It was declared that formation of meta-stable states of adsorbate in fixed mesopores on external surfaces or in the internal voids of soil organic matter was largely responsible for the great entrapment of PAHs in humin [7]. However, it was also suggested that pore deformation plays a major role to the observed hysteresis in kerogen compared to physical entrapment of sorbate molecules [36].…”
Section: Possible Mechanisms Contributing To Desorption Resistancementioning
confidence: 99%
“…Previous studies of the effects of aging on mechanism-specific sorption and desorption have documented that aging time would lead to higher solute retention, reduced desorption, and less extractability with organic solvents that resulted from greater contaminant sequestration or binding [3][4][5]. Although some studies argued that reported sorption/desorption hysteresis phenomena may be due to experimental artifacts resulting from non-attainment of sorption equilibrium before desorption experiments, which were conceptualized as ''pseudo-hysteresis'' [6], true hysteresis phenomenon has been distinguished from artificial hysteresis by many researchers [7][8][9]. Sander et al eliminated common artificial causes by the method of quantifying hysteresis thermodynamically and found that true sorption hysteresis was significant in the peat and the coal [7], and others also confirmed irreversible sorption of neutral hydrocarbons to sediments in cyclic adsorption/ desorption studies [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of desorption hysteresis was quantified using the thermodynamic index of irreversibility (TII) proposed by Sander et al (2005). Usually, the calculated TII values lies in the range of 0 to 1, where the value 1 indicating the maximum irreversibility.…”
Section: Sorption and Desorption Of Pfos To Humic Acid At Different Tmentioning
confidence: 99%
“…On the other hand, the desorption isotherms significantly deviate from the corresponding adsorption isotherms, indicating that adsorption of Zn(II) onto TiO 2 was not fully reversible. The thermodynamic index of irreversibility (TII) proposed by Sander et al [38] was used to quantify the adsorption irreversibility. The TII was defined as the ratio of the observed free energy loss to the maximum possible free energy loss due to sorption hysteresis, which was given by where C S eq is the solution concentration of the adsorption state S (C S eq , q S eq ) from which desorption is initiated; C D eq is the solution concentration of the desorption state D (C D eq , q D eq ); C γ eq is the solution concentration of hypothetical reversible desorption state γ (C γ eq , q γ eq ).…”
Section: Adsorption-desorption Isotherms and Hysteresismentioning
confidence: 99%